Exercises on inference making designed for grade four pupils - Aguilar, Annabella Sazon 1945- (1977)
This study is an attempt to construct instructional materials on inference making for grade four pupils designed to alter the culture-bound Reading for Understanding Skill Builders Series. Only four items were selected from the original sixty items to form the final set of exercises. Passages with satisfactory and good discrimination indices were included. Each item was closely examined and reviewed.
"May, 1977."
Vita.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.
Keywords: Reading (Elementary) -- Philippines -- Problems, exercises, etc; Teaching -- Philippines -- Aids and devices